Characterization of the Drosophila adenosine receptor: the effect of adenosine analogs on cAMP signaling in Drosophila cells and their utility for in vivo experiments - Kucerova, Lucie; Broz, Vaclav; Fleischmannova, Jana; Santruckova, Eva; Sidorov, Roman; Dolezal, Vladimir; Zurovec, Michal (Journal of neurochemistry, 2012)
Adenosine receptors (AR) belonging to the G protein-coupled receptor family influence a wide range of physiological processes. Recent elucidation of the structure of human A2AR revealed the conserved amino acids necessary for contact with the Ado moiety. However, the selectivity of Ado analogs for AR subtypes is still not well understood. We have shown previously that the Drosophila adenosine receptor (DmAdoR) evokes an increase in cAMP and calcium concentration in heterologous cells. In this study, we have characterized the second-messenger stimulation by endogenous DmAdoR in a Drosophila neuroblast cell line and examined a number of Ado analogs for their ability to interact with DmAdoR. We show that Ado can stimulate cAMP but not calcium levels in Drosophila cells. We found one full and four partial DmAdoR agonists, as well as four antagonists. The employment of the full agonist, 2-chloroadenosine, in flies mimicked in vivo the phenotype of DmAdoR over-expression, whereas the antagonist, SCH58261, rescued the flies from the lethality caused by DmAdoR over-expression. Differences in pharmacological effect of the tested analogs between DmAdoR and human A2AR can be partially explained by the dissimilarity of specific key amino acid residues disclosed by the alignment of these receptors.
Keywords: vápníková signalizace; Animals; Real-Time Polymerase Chain Reaction; AMP cyklický; křečci praví; vztah mezi dávkou a účinkem léčiva; Adenosine; buněčné linie; pyrimidiny; CHO buňky; Receptors, Purinergic P1; sekvence aminokyselin; triazoly; Drosophila; adenosin; lidé; Molecular Sequence Data; purinergní receptory P1; signální transdukce; přežití; Amino Acid Sequence; vápník; Signal Transduction; Cricetulus; Cell Line; molekulární sekvence - údaje; Cyclic AMP; Dose-Response Relationship, Drug; Calcium; Triazoles; 2-Chloroadenosine; Calcium Signaling; 2-chloradenosin; Survival; Amino Acids; zvířata; aminokyseliny; kvantitativní polymerázová řetězová reakce; Cricetinae; Pyrimidines; CHO Cells; Humans